2001
DOI: 10.1063/1.1344919
|View full text |Cite
|
Sign up to set email alerts
|

Neutron emission from a deuterated solid target irradiated by an ultraintense laser pulse

Abstract: Neutron production from a deuterated solid target irradiated by an ultraintense laser pulse is studied by means of kinetic numerical simulations. A two-dimensional particle-in-cell code is used to compute the velocity distribution of the deuterium ions accelerated during the interaction of the laser pulse with a hot deuterium plasma. A postprocessor has been designed to evaluate the slowing down of these ions in the solid unionized target, and the amount of neutrons produced by nuclear reactions between the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…The other source of neutrons e.g. electro disintegration of D atoms or photo dissociation of D or C atoms as well as other beam target reaction are expected to have negligible contribution in our relatively low intensity laser irradiation condition [11,12]. Here it is also important to note that for the low contrast laser, as in our case, deuterium ions are essentially accelerated in radial direction and it is observed that neutrons are emitted isotropically (or with weak anisotropy) [7].…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…The other source of neutrons e.g. electro disintegration of D atoms or photo dissociation of D or C atoms as well as other beam target reaction are expected to have negligible contribution in our relatively low intensity laser irradiation condition [11,12]. Here it is also important to note that for the low contrast laser, as in our case, deuterium ions are essentially accelerated in radial direction and it is observed that neutrons are emitted isotropically (or with weak anisotropy) [7].…”
Section: Methodsmentioning
confidence: 88%
“…Here it is also important to note that for the low contrast laser, as in our case, deuterium ions are essentially accelerated in radial direction and it is observed that neutrons are emitted isotropically (or with weak anisotropy) [7]. In contrast, for a high contrast laser pulses, the deuterons are mainly accelerated in forward direction and in this case the neutron anisotropy will be large [11,12].…”
Section: Methodsmentioning
confidence: 96%
“…Neutron yields from the dual target configuration are calculated in a similar manner to previous studies [4,5,6,7,10]. The model uses a Monte-Carlo method by randomly selecting individual deuterium ions from the specified incident ion spectrum.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…As the incident deuterium ion penetrates a distance dx into the target, the neutron flux contribution over that distance is given by [4,6]:…”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation